Prevalence of Mycoplasma agalactiae and Toxoplasma gondii in goats and sheep in La Guajira and Cesar, Colombia - Domínguez-Amorocho, Omar (2021)
The aim of this study was to determine the prevalence of Toxoplasma gondii and Mycoplasma agalactiae in sheep and goats from the south of La Guajira and north of Cesar as part of the establishment of a serological profile of these species in the Colombian region. Serum samples (n=1039) were analysed with commercial ELISA kits specific for these pathogens. The global prevalence found in the region was 25.1 and 18.3% for T. gondii and 0.12 and 0.8% for M. agalactiae in sheep and goats, respectively. Positive samples for T. gondii were more frequent in females than in males. Likewise, all samples positive for M. agalactiae were determined in females.